2010
DOI: 10.1186/1471-2199-11-65
|View full text |Cite
|
Sign up to set email alerts
|

Two storage hexamerins from the beet armyworm Spodoptera exigua: Cloning, characterization and the effect of gene silencing on survival

Abstract: BackgroundIn insects, hemocyanin superfamily proteins accumulate apparently to serve as sources of amino acids during metamorphosis, reproduction and development. Storage hexamerins are important members of the hemocyanin superfamily. Although insects possess storage hexamerins, very little is known about the character and specific functions of hexamerin 1 and storage protein 1 in insect development.ResultsTo gain insight into the function of storage proteins in insects, cDNAs for two storage proteins were clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
1
29
0
Order By: Relevance
“…Further investigations on the tissue distribution revealed that Ap-hexamerin was also expressed at a non-negligible level in the epidermis and Malpighian tubule but rarely detected in the midgut and haemocytes under physiological conditions (Figure 2b-d). This result coincides with that of hexamerin in the beet armyworm, Spodoptera exigua, in which hexamerin was detected in the fat body, Malpighian tubule, cuticle, and midgut (Tang et al, 2010). Recently, two studies on honeybees showed the intranuclear localization of hexamerins in sexual organs, probably functioning as nucleolus proteins in developing and mature (Martins & Bitondi, 2016;Martins, Anhezini, Dallacqua, Simoes, & Bitondi, 2011).…”
Section: Pattern Recognition Properties Of Ap-hexamerinsupporting
confidence: 84%
See 1 more Smart Citation
“…Further investigations on the tissue distribution revealed that Ap-hexamerin was also expressed at a non-negligible level in the epidermis and Malpighian tubule but rarely detected in the midgut and haemocytes under physiological conditions (Figure 2b-d). This result coincides with that of hexamerin in the beet armyworm, Spodoptera exigua, in which hexamerin was detected in the fat body, Malpighian tubule, cuticle, and midgut (Tang et al, 2010). Recently, two studies on honeybees showed the intranuclear localization of hexamerins in sexual organs, probably functioning as nucleolus proteins in developing and mature (Martins & Bitondi, 2016;Martins, Anhezini, Dallacqua, Simoes, & Bitondi, 2011).…”
Section: Pattern Recognition Properties Of Ap-hexamerinsupporting
confidence: 84%
“…Most of the storage proteins are identified as hexamerins, a group of respiratory hemocyaninderived proteins that lost the ability to transport oxygen (Burmester, 2002;Telfer & Kunkel, 1991). A number of hexamerins have been identified in arthropods (Burmester, 2015;Cristino et al, 2010;Cunha, Nascimento, Guidugli, Simoes, & Bitondi, 2005;Liang, Xie, & Luan, 2019;Martins & Bitondi, 2012;Pick, Hagner-Holler, & Burmester, 2008;Tsai, Chen, & Tsai, 2014), but research in recent decades has demonstrated that in addition to providing energy as storage proteins in the nonfeeding stage, hexamerins also take part in many other physiological processes, including egg production (Wheeler, Tuchinskaya, Buck, & Tabashnik, 2000), hormone transport (Ashfaq, Sonoda, & Tsumuki, 2007;Rao, Ningshen, Chaitanya, Senthilkumaran, & Dutta-Gupta, 2016), caste regulation (Hawkings, Calkins, Pietrantonio, & Tamborindeguy, 2019;Zhou, Tarver, Bennett, Oi, & Scharf, 2006), diapause (Spiliotopoulos, Gkouvitsas, Fantinou, & Kourti, 2007), and even immune responses (Fallon, Troy, & Kavanagh, 2011;Poopathi et al, 2014;Tang, Wang, & Zhang, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…5). In contrast, knockdown of two important storage proteins, SeHex and SeSp1 in Spodoptera exigua resulted in increased mortality, suggested to be caused by a lack of nutritional reserves46. However, in this study, we only targeted the group of hexamerins that were upregulated in the gut after PI ingestion.…”
Section: Resultsmentioning
confidence: 98%
“…RNAi experiments have been conducted on insects that belong to different taxonomic groups, particularly Holometabolous insects: Lepidopterans; Bombyx mori , Manduca sexta , Helicoverpa armigera [41], Spodoptera Exigua [23], [42] Plutella xylostella [26], dipterans; D. melanogaster , Bactrocera Dorsalis [43], and coleopterans; Diabrotica virgifera [44], [45]. Fewer studies have been carried out on Hemimetabolous insects: Isoptera; termite Reticulitermes flavipes [46], Orthoptera; Locusta migratoria [47] Gryllus bimaculatus [40]; Hemiptera and Homoptera; Rhodnius prolixus [48], Nilaparvata lugens [49], [50], Laodelphax striatellus [50], Bemisia tabaci [51] Bacterocera cockerelli [52] and Acyrthosiphon pisum [53].…”
Section: Introductionmentioning
confidence: 99%